Transcriptome analysis of Colletotrichum nymphaeae-Strawberry interaction reveals in planta expressed genes associated with virulence - Ozbudak, Egem; Carrillo-Tarazona, Yisel; Diaz, Edinson A.; Zambon, Flavia T.; Rossi, Lorenzo; Peres, Natalia A.; Raffaele, Sylvain; Cano, Liliana M. (Frontiers in Plant Science, 2025)
Colletotrichum nymphaeae, the causal agent of anthracnose fruit rot, is recognized as the second most important pathogen of strawberries in the globe due to its economic impacts. Fungal pathogens deploy various sets of secreted proteins that have crucial roles in compatible interactions with the plant hosts, including acquiring host nutrients or suppressing host immunity. Therefore, transcriptomic studies are critical to determining the genes expressed explicitly during plantpathogen interactions. In this study, we performed RNAseq profiling of Colletotrichum nymphaeae during infection in leaf and fruit tissues of the susceptible strawberry (Fragaria x ananassa) cultivar Florida Beauty. The transcriptomic profiling of C. nymphaeae 02-179 during infection in strawberries, revealed genes encoding for secreted effector proteins such NUDIX hydrolase domain and LysM domain containing proteins. We also found upregulated genes encoding for Carbohydrate-Active enzymes (CAZymes) such Multicopper oxidase, Pectinesterase, Pectate Lyase, Glycosyl hydrolase family 7, and Endochitinase proteins. Among all up-regulated genes, we highlight a two novel Tannases with potential roles in the development of anthracnose disease, as the top upregulated genes in strawberry-infected leaves and fruits samples. Fungal Tannase enzymes can potentially degrade tannins, plant secondary metabolites abundantly found in strawberries and well known for their protective roles against pests or pathogens in plants. Further functional analyses of this gene family can shed light on determining the disease mechanism and improve disease management strategies. Commented [LC1]: Minor edit: 1) We have included another affiliation to the first author, Egem Ozbudak, noted in the track changes in lines 5-6. Commented [LC2]: Minor edit: We have removed "Douglas S. Stuehler Jr." from the co-author list and added his name in the acknowledgments section of the manuscript instead in lines 676-678. Deleted: We thank Douglas S. Stuehler Jr. from the USDA ARS 696 Horticultural Research Lab for his technical assistance with RNAseq 697 read data.